(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2013)
Pressure ulcer (PU) is a serious health problem with serious health, economic, ethical and legal consequences. These wounds have been a concern of nursing, especially when it comes to hospitalized patients with impaired mobility. The study aimed todetermine the incidence and prevalence of PUs among inpatients in a university hospital in São Luís, MA, Brazil. This was a quantitative, exploratory, cross-sectional and prospective, epidemiological study. Prevalence rates were calculated for two different days. Theprevalence of PUswas 43.9% on November 30, 2009 and 42.7% on April 30, 2010. Although constant over time, the prevalence rates of PUs found in this studywere high. Theincidence of PUswas 21.5%, which is low compared to those of previous Brazilian studies. Although relatively low, this rate still needs to be reduced, as PUs are identified as an indicator of poor-quality care. Data on the incidence andprevalence of PUs in the university hospital of São Luís (MA) show theextent of the problemand should encouragenursesto implementa comprehensive program to prevent these wounds.